The creation and validation of a listening vocabulary levels test. (November 2015) - McLean, Stuart; Kramer, Brandon; Beglar, David
An important gap in the field of second language vocabulary assessment concerns the lack of validated tests measuring aural vocabulary knowledge. The primary purpose of this study is to introduce and provide preliminary validity evidence for the Listening Vocabulary Levels Test (LVLT), which has been designed as a diagnostic tool to measure knowledge of the first five 1000-word frequency levels and the Academic Word List (AWL). Quantitative analyses based on the Rasch model utilized several aspects of Messick's validation framework. The findings indicated that (1) the items showed sufficient spread of difficulty, (2) the majority of the items displayed good fit to the Rasch model, (3) items and persons generally performed as predicted by a priori hypotheses, (4) the LVLT correlated with Parts 1 and 2 of the TOEIC listening test at .54, (5) the items displayed a high degree of unidimensionality, (6) the items showed a strong degree of measurement invariance with disattenuated Pearson correlations of .97 and .98 for person measures estimated with different sets of items, and (7) carelessness and guessing exerted only minor influences on test scores. Follow-up interviews and qualitative analyses indicated that the LVLT measures the intended construct of aural vocabulary knowledge, the format is easily understood, and the test has high face validity. This test fills an important gap in the field of second language vocabulary assessment by providing teachers and researchers with a way to assess aural vocabulary knowledge.